Environmental Histories of Mediterranean Fascisms - Guimarães, Paulo Eduardo (2021)
This special issue aims to explore the environmental dimension and engagement of Mediterranean fascist regimes inclusive of their colonial possessions. Methodologically, this implies to go beyond the narrow understanding of environmental history as a discipline putting at the centre of its analysis natural or ecological elements and to bridge environmental history with political and social history, and other historical subfields. Among the many themes touched in this volume, we would like to stress three more significant and overarching issues: reclamation as a material and ideological regeneration of people and places; modernity as the ideology through which fascist regimes employed science and technology to create socio-ecologies at the service of their goals; and colonization (internal and external) as the concrete laboratory where reclamation and modernity were experimented as forms of control, regime-building, and oppression. Blending fascist studies and environmental history sounds like an unconventional scholarly enterprise. Seemingly, this is because the former addresses complex and contradictory mixtures of traditionalism, racial and scientific positivism, anti-liberalism, corporatism, authoritarianism, but also modernist ideologies and innovative forms of mass communication and mobilization. Whereas the latter is an academic discipline attentive to processes of natural depletion and conservation, and, we might argue, also considered quite progressive. Even more than that, fascist studies and environmental history form an odd couple because the first line of enquiry is actually one of the most well-established areas of interest for historians of modern times, while the latter is often seen as a rather marginal or emerging field of studies, especially in the Mediterranean countries. Finally, fascist and environmental histories form an unusual combination because according to traditional sub-disciplinary boundaries, environmental historians should not be concerned about themes like fascism. Quite the opposite, they should dedicate themselves to the confined niche of "the environment" (Armiero 2016). In this sense, our special issue questions the narrow understanding of "the environment" and propose a vision of our discipline not in terms of themes but rather of perspectives.